2019
DOI: 10.1108/ijmpb-09-2018-0200
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing project management effectiveness in the Malaysian local councils

Abstract: Purpose The purpose of this paper is to examine the relationship between top management support, project mission (PM), synergy and project management effectiveness (PME) in the Malaysian local councils. It also attempts to analyze the relative importance and performance of the predictor constructs on the target construct for managerial actions. Design/methodology/approach Primary data based on 169 respondents were collected and analyzed using PLS-SEM to assess validity, reliability, hypothesis testing and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The UK Association of Project Management defines effectiveness differently. It describes project management as a process of planning, controlling, evaluating, analysing and regulating every aspect of a project to meet objectives precisely and within the timeline, budget and overall quality constraints [11]. Ultimately, effectiveness is not the extent of how successfully a company and its workers accomplish valuation operations, but rather how equally distinct roles collaborate and are synchronized [35].…”
Section: Project Management Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The UK Association of Project Management defines effectiveness differently. It describes project management as a process of planning, controlling, evaluating, analysing and regulating every aspect of a project to meet objectives precisely and within the timeline, budget and overall quality constraints [11]. Ultimately, effectiveness is not the extent of how successfully a company and its workers accomplish valuation operations, but rather how equally distinct roles collaborate and are synchronized [35].…”
Section: Project Management Effectivenessmentioning
confidence: 99%
“…Furthermore, this study investigates top management support as the confining form for humble leadership to influence project management effectiveness. Standing concepts and studies directly state that project managers and senior management assistance are simultaneously significant in project management effectiveness [11]. Previous research has emphasized that superior management support is critical at various project stages [12].…”
Section: Introductionmentioning
confidence: 99%
“…The study's findings suggested that humility is an essential trait for a project manager to guarantee the effectiveness of the project management. Furthermore, the current research covers the gap highlighted by earlier researchers that the literature on project management does not adequately define the leadership styles of the project manager in project management effectiveness 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Such humble leadership behaviour improves follower morale and enhances the open sharing of ideas through feedback 28 . It will create an environment where followers tend to focus on addressing their deficiencies to meet performance requirements, allowing them to work effectively and run the project management effectively 11 .…”
Section: Humble Leadership and Project Management Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation